2020
DOI: 10.1088/1757-899x/918/1/012200
|View full text |Cite
|
Sign up to set email alerts
|

Features of risk management in the construction industry in a pandemic with limited use of transport

Abstract: The article highlights the main risks faced by construction companies in a pandemic with limited use of transport. At the same time, one of the significant leaps in the development of companies is updating information technologies that require a new approach with limited possible information transfer between employees. So an important factor in the impact of crisis is the work of office workers on remote access. The article presents the testing of proposed recommendations for evaluating workers in terms of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…During the lockdown period, managing project teams working from home became challenging [27]. Minnullina et al [58] suggested that revisiting management decisions plays a critical role in minimizing risks in terms of enhancing employee reliability. The interviewees also mentioned that COVID-19 has already changed many things at the workplaces.…”
Section: A Covid-19 Challenges 1) Productivity and Organizational Cha...mentioning
confidence: 99%
See 3 more Smart Citations
“…During the lockdown period, managing project teams working from home became challenging [27]. Minnullina et al [58] suggested that revisiting management decisions plays a critical role in minimizing risks in terms of enhancing employee reliability. The interviewees also mentioned that COVID-19 has already changed many things at the workplaces.…”
Section: A Covid-19 Challenges 1) Productivity and Organizational Cha...mentioning
confidence: 99%
“…For example, project executors have tried to reduce the workforce on site while supporting remote work for certain processes. However, the remote working method causes the personnel to slow down [58]. Jallow et al [27] indicated that management, communication, health and safety are the most important factors for current workforce protection.…”
Section: ) Project and Resource Related Challenges (C2)mentioning
confidence: 99%
See 2 more Smart Citations
“…Simple access to the market of services through Internet platforms leads to the destruction of traditional business schemes, which include a large number of intermediaries. Minnullina et al (2020) believe that intermediaries' withdrawal from business can lead to a decrease in the number of economic entities that also used to bring income to the state, to financial losses in industries with a traditional model because they do not withstand competition. Besides, the number of unemployed grows and there is an increase in sales of prohibited goods and low-quality goods.…”
mentioning
confidence: 99%